Possibilities of cloud educational technologies in the study of physical chemistry - D. G. Naryshkin (Academy of Cognitive and Natural Sciences, 2013)
Opening of Mathcad Calculation Server (MCS) (http://www.vpu.ru/mas) at the Moscow Power Engineering Institute made it possible to create and implement an interactive reference book of physico-chemical quantities and thermodynamic database (http://twt.mpei.ac.ru/TTHB/1/HBThermValues.html) in the remote access mode in the educational process. Such authoritative electronic databases as, for example, the Database of Iftantermo, NIST Chemistry WebBook allow to obtain individual numbers or arrays of numbers characterizing the properties of substances and systems, but they do not generate functional and graphical relationships, which significantly reduces their educational opportunities. The peculiarity of interactive web-version of physicochemical quantities is its educational orientation: each Mathcad-document specifies by which experimental data the analytical dependence describing change of the investigated function was made, by which relations and how the investigated parameter is calculated, dependence diagrams are given, that allows to observe behavior of the searched quantity and current point on curve.